Clinical Effectiveness of Free Upper Arm Medial Flap in Repairing Skin and Soft Tissue Defects of the Dorsum of the Hand. (26th June 2022) - Yu, Xuejun; Zheng, Wen; An, Wei; Xiang, Shengtao; Zhao, Linglong
Abstract : Objective . To study the effectiveness of medial upper arm free flap in repairing skin and soft tissue (SST) defects of the dorsum of the hand. Methods . 10 patients with SST defects on the dorsum of the hand who underwent free upper arm medial flap repair in our hospital from March 2017 to August 2018 were included in the study. Hand function, flap survival rate, wound healing, donor wound recovery, and the level of pain in the injured area were recorded before the operation, 1 month, and 6 months postoperatively. Results . The highest score in hand function was seen at the 6-month postoperative interval, followed by that at the 1-month postoperative interval. The lowest score in hand function was the preoperative score (P < 0.05 ). All flaps were still surviving 6 months postoperatively. Recovery of the function of the donor muscle, the elbow joint, as well as wound healing, all progressed well. 6 months postoperatively, 3 patients developed numbness and stiffness of the hand, but the symptoms were relieved following treatment. Compared to the preoperative scores, the visual analogue scale (VAS) scores at the injured site 1 month and 6 months postoperatively were significantly decreased, with the 6-month postoperative score being lower than the 1-month postoperative score (P < 0.05 ). Conclusion . The free upper arm medial flap is a good alternative for repairing skin and soft tissue defects of the dorsum of the hand with exposed phalanges, an approach that merits widespread promotion and clinical application.